Age Differences in Perceptions of and Motivations for Voluntary Medical Male Circumcision Among Adolescents in South Africa, Tanzania, and Zimbabwe. (3rd April 2018) - Patel, Eshan U; Kaufman, Michelle R; Dam, Kim H; Van Lith, Lynn M; Hatzold, Karin; Marcell, Arik V; Mavhu, Webster; Kahabuka, Catherine; Mahlasela, Lusanda; Njeuhmeli, Emmanuel; Seifert Ahanda, Kim; Ncube, Getrude; et al.
Abstract: Background: The World Health Organization (WHO) and the Joint United Nations Programme on HIV/AIDS (UNAIDS) have set a Fast-Track goal to achieve 90% coverage of voluntary medical male circumcision (VMMC) among boys and men aged 10–29 years in priority settings by 2021. We aimed to identify age-specific facilitators of VMMC uptake among adolescents. Methods: Younger (aged 10–14 years; n = 967) and older (aged 15–19 years; n = 559) male adolescents completed structured interviews about perceptions of and motivations for VMMC before receiving VMMC counseling at 14 service provision sites across South Africa, Tanzania, and Zimbabwe. Adjusted prevalence ratios (aPRs) were estimated using multivariable modified Poisson regression models with generalized estimating equations and robust standard errors. Results: The majority of adolescents reported a strong desire for VMMC. Compared with older adolescents, younger adolescents were less likely to cite protection against human immunodeficiency virus (HIV) or other sexually transmitted infections (aPR, 0.77; 95% confidence interval [CI], .66–.91) and hygienic reasons (aPR, 0.55; 95% CI, .39–.77) as their motivation to undergo VMMC but were more likely to report being motivated by advice from others (aPR, 1.88; 95% CI, 1.54–2.29). Although most adolescents believed that undergoing VMMC was a normative behavior, younger adolescents were less likely to perceive higher descriptive norms (aPR, 0.79; .71–.89), injunctive norms (aPR, 0.86; 95% CI, .73–1.00), or anticipated stigma for being uncircumcised (aPR, 0.79; 95% CI, .68–.90). Younger adolescents were also less likely than older adolescents to correctly cite that VMMC offers men and boys partial HIV protection (aPR, 0.73; 95% CI, .65–.82). Irrespective of age, adolescents' main concern about undergoing VMMC was pain (aPR, 0.95; 95% CI, .87–1.04). Among younger adolescents, fear of pain was negatively associated with desire for VMMC (aPR, 0.89; 95% CI, .83–.96). Conclusions: Age-specific strategies are important to consider to generate sustainable demand for VMMC. Programmatic efforts should consider building on the social norms surrounding VMMC and aim to alleviate fears about pain.